How vlogging can build seafarer candidate self-confidence in speaking English (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
In 1973 the IMO Sea Security Committee concurred at its twenty-seventh session that English has been used as a common language for navigational purposes. Mix nation languages and lack of proper English communication skill onboard become barriers which had contributed to marine safety and even loss of property onboard. In consequence, seafarer candidates must be able to speak English well so they can avoid misunderstanding on shore-to-ship (and vice versa), ship-to-ship and on-board communications. Nevertheless, this skill becomes a crucial problem for some seafarer candidates who have lack confidence in speaking English. This study was conducted to investigate how vlogging could build the seafarer candidates’ English speaking skills whilst they had a lack of confidence. This research used descriptive qualitative research. It was conducted at Politeknik Maritim Negeri Indonesia. The samples of this study were 28 Marine Engineering students in the third semester. They were from A and B classes. This research used three techniques in collecting data namely questionnaire, observation, and interview. The questionnaire was given in an online form which contained 10 questions. To analyze the data, the writer used Likert scale. The writer also managed observation and an interview by giving them 10 open-ended questions. To support the data, the writer also analyzed the video result. The result of the study showed that Vlogs can be used to improve the seafarer candidate's confidence in speaking English.